Effectiveness of growth strategies adopted by microfinance institutions (MFIS) on financial performance: A case of MFIs IN Midlands Province. - Kanukai, Tawanda (Midlands State University, 2017)
Studies on performance of microfinance institutions (MFIs) has attracted a great deal of attention as they are registering a significant growth in the financial landscape. However most of these studies had focused much on social performance and best credit management practices and regrettably ignored the financial aspects. This is because predominantly, the main objective of MFIs was social mission focusing on poverty alleviation and financial inclusion, however the 21st century signifies a drift from social mission to profit maximization hence the call to consider financial aspects. Growth strategies are key performance drivers yet little attention has been given to their influences. MFIs are engaging in market expansion overdrive giving birth to intense and unhealthy competition that is not bringing positive results to both the institutions and stakeholders. Against this backdrop, the sustainability of these institutions is threatened hence this study examined the effectiveness of growth strategies adopted by microfinance institutions on profitability in Midlands province. Return on Assets (ROA) and Return on Equity (ROE) were used as profitability measures while number of branches was used to determine growth strategies adopted. Literature put forward by different scholars regarding the influence of growth strategies on organization’s performance was critically reviewed. The study applied descriptive research design to identify growth strategies adopted by MFIs in their pursuit for growth and correlational research design to examine the effectiveness of each growth strategy on profitability through the use of simple linear regression. Stratified random sampling technique was employed to adequately incorporate views from different angles since research subjects were drawn from different stratas (senior management and branch managers). Sample size of 79% of the target population was obtained from a list of appropriate sample sizes that are good enough to produce credible findings calculated by Krejcie and Morgan (1970). The study used both questionnaires and personal interviews to collect relevant data to ensure that validity and reliability was achieved. Findings from the study revealed that MFIs chose to go it alone by opting for organic growth with most of them pursuing market development growth strategy. Market growth strategy proved to be ineffective on profit enhancement in microfinance context, rather it causes intense and unhealthy competition hurting both parties (Institutions and stakeholders). Results from the study revealed that there is a relationship between age of MFI and the growth strategy pursued, where most young aged MFIs are investing much in market growth while the old horses appreciate market penetration growth strategy. The results also indicated that product growth strategy is an effective path of growing that yields more returns whilst market penetration proved to have insignificant impact on profitability. In light of study findings, it is therefore recommended that MFIs should consider inorganic growth strategies such as mergers to do away with disruptive competition. Furthermore, MFIs are also recommended to embrace product development growth strategy to realize significant financial growth associated with high degree of operational efficiency and sustainability. In addition, young aged MFIs are recommended not to over invest in growing the market but rather on creating a strong bond with their clients by investing in developing a variety of products.